Long‐term safety and efficacy of glucagon‐like peptide‐1 receptor agonists in individuals with obesity and without type 2 diabetes: A global retrospective cohort study - Huang, Yu‐Nan; Liao, Wen‐Ling; Huang, Jing‐Yang; Lin, Yu‐Jung; Yang, Shun‐Fa; Huang, Chieh‐Chen; Wang, Chung‐Hsing; Su, Pen‐Hua (Diabetes, obesity & metabolism, 2024)
Aim We aimed to investigate the long‐term impact of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) on thyroid function, cardiovascular health, renal outcomes and adverse events in individuals with obesity and without type 2 diabetes (T2D). Materials and Methods In this observational cohort study, we used propensity score matching to construct comparable cohorts of individuals with obesity and without T2D who were new to GLP‐1 RA treatment and those who did not receive glucose‐lowering medications. In total, 3,729,925 individuals with obesity were selected from the TriNetX Global Network, with an index event between 1 January 2016 and 31 March 2024. The primary outcomes were safety, cardiovascular, thyroid and clinical biochemical profile outcomes occurring within 5 years following the index event. Results After propensity score matching, the study included 12,123 individuals in each group. GLP‐1 RA treatment was associated with a significantly lower risk of all‐cause mortality (hazard ratio 0.23; 95% confidence interval 0.15–0.34) and several cardiovascular complications, including ischaemic heart disease, heart failure, arrhythmias, hypertension, stroke and atrial fibrillation (all p < 0.05). GLP‐1 RAs were also associated with a lower risk of acute kidney injury and allergic reactions. These protective effects were consistent across various subgroups and regions. Conclusions In this large observational study, GLP‐1 RAs showed long‐term protective effects on cardiovascular health, renal outcomes and adverse events in individuals with obesity and without T2D. Our findings suggest that GLP‐1 RAs may offer a comprehensive approach to managing obesity and its related comorbidities, potentially improving overall health and survival in this population.